NOUN. NUMERALS. CONJUGATION OF IMPERFECT VERBS OF THE FIRST CONJUGATION IN THE PRESENT TENSE. LEXICAL TOPIC: INTERESTS AND PLANS. MY DAY (Web of Teachers: Inderscience Research, 2026)
This article presents the development of a practical lesson based on the developed methodology for first-year students majoring in "Theory and Practice of Translation (English)" at the Alisher Navoiy Tashkent State University of the Uzbek Language and Literature. The goal of the lesson is to repeatedly practice verbs that are conjugated by analogy, which facilitates rapid understanding and memorization, as well as active use of these verbs in oral and written communication.